Pengurusan Penyelenggaraan dan Penyediaan Fasiliti di Bangunan Terminal Bas Batu Pahat, Johor - Ahmad Taha, Muhammad Faiz (Research in Management of Technology and Business, 2021)
Facilities maintenance for bus terminal in Batu Pahat was already being an issues due to the facilities provided are not well maintenance including the toilets, elevators, signboards, appliances and so on. The provision of available facilities needs to be maintained because it can ensure the cleanliness of the environment. Besides, the objectives of this study are to identify the issues regarding the management of facilities maintenance and to assess the level of user satisfaction on the provision of facilities at the Batu Pahat Bus Terminal. Through this objectives, the study use a quantitative and qualitative methods by distributing questionnaires to respondents of Batu Pahat Bus Terminal and It consists of 50 participants to obtain the information. Other than that, the researchers had interviewed stakeholders that were related to the bus terminal operation such as MPBP, JMB and contractor. Moreover, the observation's method also had been used by the researcher to gain more insight and data regarding the field sites. The results of this study can be seen through the management efforts in which to manage the facilities in the building with more systematic with quality facilities in meeting the level of users satisfaction. In this study, the researcher has provided some views and suggestions on Batu Pahat Bus Terminal such as to implement a regular maintenance and to ensure users comfort if a good and best satisfactory.